ANTHROPOLOGISTS IN THE VA: A GENERATIVE FORCE. Issue 2 (November 2013) - Sobo, Elisa J.; Besterman‐Dahan, Karen; Hamilton, Alison
<x xml:space="preserve">Abstract</x> Practicing anthropology within the Veterans Health Administration of the Department of Veterans Affairs (VA) has, until recently, received little serious consideration as a respectable career option for anthropology postgraduates. But times are changing. Anthropologists employed by the VA are responsible for some of the most important and actionable anthropologically informed health research today. Far from being a marginal pursuit, VA anthropology is in fact a generative force for medical anthropology and, indeed, the discipline as a whole.